Impact of Resilience on Patient Reported Outcomes of First Metatarsophalangeal Arthrodesis. Issue 1 (January 2022) - Andrews, Nicholas A.; Tran, Sterling; Halstrom, Jared R.; Ray, Jessyca; Harrelson, Whitt; Dib, Aseel G.; Agarwal, Abhinav; Shah, Ashish
Category: Other; Ankle; Midfoot/Forefoot Introduction/Purpose: Resilience is an interactive dynamic construct most simply defined as the ability to recover from stress. To date, there is no literature examining the impact of resilience on the outcomes following foot and ankle surgery. Methods: We retrospectively reviewed patients who underwent first MTP arthrodesis from September 2011 to May 2020, 98 met inclusion criteria. Medical records were reviewed for patient characteristics and union status. PROMIS Physical Function (PF), Pain Interference (PI), Depression (D), and the Foot Function Index (FFI) were collected. Resilience was measured using the Brief Resilience Scale. A multivariable linear regression analysis examining the impact of resilience on patient reported outcomes while adjusting for potential confounding covariates was conducted. Results: At an average of 3.4+-2.6 (SD) years postoperatively, resilience was found to have an independent effect on patient reported outcomes across all instruments, except the FFI pain subscale. Resilience's effect on the instruments was as follows: PROMIS physical function (Unstandardized β 5.0, 95% CI 2.6 to 7.4), PROMIS pain interference (Unstandardized β -4.8, 95% CI - 7.8 to -1.8), PROMIS Depression (Unstandardized β -9.4, (95% CI -12.8 to -6.1), FFI disability subscale (Unstandardized beta -13.3, 95% CI -20.3 to -6.3 ), FFI activity limitation subscale (Unstandardized beta -15.7, 95% CI -23.0 to -8.5), FFI total (Unstandardized beta -11.7, 95% CI -18.1 to -5.4), and FFI pain subscale (Unstandardized beta -6.5, 95% CI -13.1 to.01). Conclusion: In this first study examining the impact of resilience following foot and ankle surgery, we found that resilience has an independent positive effect on overall physical function, disability, pain, and mental health following MTP arthrodesis. Preoperative resilience scores could be used to predict postoperative functional outcomes following MTP arthrodesis and guide postoperative rehabilitation. These findings help establish the role of early positive psychosocial characteristics within orthopaedic foot and ankle population.